2020
DOI: 10.1039/c9cy02579k
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the simultaneous removal of COS, CS2and O2from coke oven gas by hydrogenation on a Pd/Al2O3catalyst

Abstract: Simultaneous hydrogenation of organosulfur compounds and O2 by Pd/Al2O3 catalyst was studied in a fixed bed reactor and by DRIFTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Alumina, as a well-known industry catalyst, has been considered effective for the hydrolysis of COS in view of its abundant basic active sites, favorable surface areas, and low cost. However, a conventional alumina catalyst always exhibits poor sulfate resistance, resulting in an abrupt deactivation. This is mainly due to the sulfur/sulfate deposition and contamination, resulting in the loss of active sites and pore blocking.…”
Section: Introductionmentioning
confidence: 99%
“…Alumina, as a well-known industry catalyst, has been considered effective for the hydrolysis of COS in view of its abundant basic active sites, favorable surface areas, and low cost. However, a conventional alumina catalyst always exhibits poor sulfate resistance, resulting in an abrupt deactivation. This is mainly due to the sulfur/sulfate deposition and contamination, resulting in the loss of active sites and pore blocking.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial catalysts are mostly prepared by impregnating metal components directly into a γ-Al 2 O 3 support. Kamp E. et al 48 selected Pd/Al 2 O 3 to completely convert COS into H 2 S at 200 °C, and the results showed that COS dissociated at the Pd site to form CO and S adsorbents, and COS would also adsorb onto the alumina support, thereby forming HSCO 2− . Subsequently, HSCO 2− reacts with hydroxide surface groups to form carbon dioxide and hydrogen sulfide.…”
Section: Bfg Desulfurization Application and Research Trendsmentioning
confidence: 99%
“…Moreover, the presence of heavier hydrocarbons, e.g., benzene that was produced in toluene conversion, may lead to accelerated saturation of absorbents/adsorbents as the heavy organic compounds can be easily separated along with sulfur compounds [43,44]. One of the solutions might be hydrodesulfurization (HDS), which would transform carbonyl sulfide, carbon disulfide, and sulfur dioxide back into hydrogen sulfide with the use of hydrogen and CoMo or NiMo catalysts [41]. This would create the possibility to apply typical hydrogen sulfide removal methods, yet they still would be somehow limited by the presence of heavier hydrocarbons.…”
Section: Hydrogen Sulfide Conversionmentioning
confidence: 99%